Manufacturing reorganisation at Varian Australia a case study on value-added management - Sohal, Amrik S. (Technovation)
This case study examines how Varian OSI in Melbourne, Australia, successfully applied management technologies, and discusses the limitations and benefits of those changes. Specific emphasis is given to the planning and implementation approaches used by Varian. The company is a leading manufacturer of quality scientific instruments. In the mid-1980s it was clear that its inventory and production management practices were unsatisfactory. Varian was limited in its production flexibility and delivery performance and so made the strategic decision to introduce the manufacturing management technologies of just-in-time (JIT) and total quality control (TQC). These technologies were implemented within a broader commitment to the concepts of value-added management (VAM). A pilot program was implemented and, following its success, the whole plant was transformed. Varian OSI has successfully customised these management technologies to suit the company and has subsequently achieved significant improvements in quality, flexibility and productivity.